Highly pathogenic avian influenza knowledge, attitudes, and practices study among live bird market workers in Jakarta - Indonesia - Sutanto, Yadi Cahyadi, author; Salman, M. D., advisor; Gillette, Shana C., committee member; Peel, Jennifer L., committee member (Colorado State University. Libraries, 2013)
Throughout the world, Indonesia is one of the countries most affected by the outbreak of the highly pathogenic avian influenza (HPAI) subtype H5N1. The outbreak has killed 160 out of 192 human cases during 2005 to 2012, the fatality rate being especially high in children and young adults (WHO, 2013), caused over 470 million USD in economic losses (KOMNAS, 2008a) and disrupted the lives of more than 20 million people who depend on the poultry industry (BPS, 2003) for their livelihood. Indonesia received from the international community the largest financial commitment to fight HPAI, totaling to more than 128 million USD (FAO, 2008a). Highly pathogenic avian influenza also affected the capital city of Jakarta. In an effort to minimize disruption to public health from the outbreak of HPAI, Jakarta provincial government has issued a local regulation (Peraturan Daerah) Number 4/2007 on the Control, Raising, and Distribution of Poultry in Jakarta. Despite the fact that Jakarta has a high risk of public health problems due to HPAI, there is no effective enforcement of the local HPAI control regulation in the city, thus the poultry collection sites and traditional slaughter houses continue to conduct unsafe practices of poultry slaughter. To overcome this problem, information is needed to know how much the poultry industry, especially the Live Bird Markets (LBMs), in Jakarta knows about the risk of HPAI in their community. The level of knowledge and perception of safe poultry handling practices regarding the risk of highly pathogenic avian influenza among workers in LBM can be assessed using a Knowledge, Attitudes, and Practices (KAP) Study. The results of this study illustrate that, despite being given information, LBM workers had no detailed understanding of avian influenza, had a less perceived risk of experiencing avian influenza, and had a low compliance with precautionary behaviors. As a result, biosecurity in the LBMs is woefully inadequate, increasing the threat of another serious outbreak of HPAI in poultry and perhaps in humans as well. Encouragingly, workers' interest in learning more about avian influenza was high in this survey. Therefore, designing and implementing avian influenza educational programs and measuring their effectiveness should be priorities to encourage the population to take a more active role.
Keywords: attitudes; highly pathogenic avian influenza; Indonesia; knowledge; live bird market; practices